KAPABILITAS SEKRETARIS DESA PASCA MENJADI APARATUR SIPIL NEGARA (ASN) DALAM PENYELENGGARAAN ADMINISTRASI PEMERINTAHAN DESA DI DESA KOTO SENTAJO KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI TAHUN 2015 - Ayu Hikmah Wati; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study is based on the problem of the secretary of the village post as civil state apparatus (ASN) in the village administration, especially in the village secretary in the village koto sentajo sub district sentajo raya kuantan singingi district. Attempts to find out how the capability of the post-village secretary becomes the state civil apparatus (ASN) in the of village administration through the concept of the capability of the village secretary post to become the state civil apparatus (ASN) in the administration of the village administration.. This study aims to describe the real situation in the field systematically and accurately related facts and units of research analysis, as well ad field observation based on certain data (information). Methods of data collection is done by interview, documentation, and observation in the field.The results of the study explain teh capabilities of the village secretary based on the duties and function in the administration of the village administration. Based on the concept of capability, the capability of the village secretary can be been in institutions, human resources (HR), finance, and technical resources. Unrealized budgets for the processs of village development and administartion of village administrations. The appropriate solution to solve the problem in the capability the post- goverment secretary to be the state civil servant (ASN) in administering the village administartions is to make the guidance of village lawa number 6 of 2014 with law number 32 of 2006 in the village administration guidelines.Keyword : Capability, village Administration.